1998
DOI: 10.1074/jbc.273.34.21616
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of GTP Cyclohydrolase I and Modulation of Its Activity in Rodent Mast Cells

Abstract: GTP cyclohydrolase I controls the de novo pathway for the synthesis of tetrahydrobiopterin, which is the essential cofactor for tryptophan 5-monooxygenase and thus, for serotonin production. In mouse bone marrow-derived mast cells, the kit ligand selectively up-regulates GTP cyclohydrolase I activity (Ziegler, I., Hültner, L., Egger, D., Kempkes, B., Mailhammer, R., Gillis, S., and Rödl, W. (1993) J. Biol. Chem. 268, 12544 -12551). Immunoblot analysis now confirms that this long term enhancement is caused by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 45 publications
1
35
1
Order By: Relevance
“…This interaction results in a decrease in the V max of GTPCH, which occurs via a mechanism that is noncompetitive with substrate (43)(44)(45). In addition to this mechanism of negative regulation, studies conducted in mammalian cell cultures demonstrate the stimulation of GTPCH via phosphorylation and suggest that the enzyme serves as a substrate for casein kinase II and protein kinase C (37)(38)(39). Other kinases have not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction results in a decrease in the V max of GTPCH, which occurs via a mechanism that is noncompetitive with substrate (43)(44)(45). In addition to this mechanism of negative regulation, studies conducted in mammalian cell cultures demonstrate the stimulation of GTPCH via phosphorylation and suggest that the enzyme serves as a substrate for casein kinase II and protein kinase C (37)(38)(39). Other kinases have not yet been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that mammalian GTPCH is phosphorylated (37)(38)(39), and we have found that the activity of recombinant Drosophila GTPCH activity is elevated when it is phosphorylated either by protein kinase A or C (21). To determine whether the phosphorylation of these enzymes had any effect on their association or, conversely, whether their association affected their regulation by phosphorylation, we first expressed and purified recombinant Drosophila TH and GTPCH isoforms B and C. We then phosphorylated the enzymes with either protein kinase C or A (both have similar effects on the activity of these enzymes) and immunoprecipitated the proteins with either anti-TH or anti-GTPCH polyclonal antibodies.…”
Section: Tyrosine Hydroxylase and Gtp Cyclohydrolase I Physicallymentioning
confidence: 97%
“…After 72-h postfertilization, however, GTP cyclohydrolase I activity does not correlate with the onset of rapid production of pteridine pigments. In mammalian cells, various cytokines and growth factors regulate the activity of GTP cyclohydrolase I at the transcriptional or post-transcriptional level (55)(56)(57), through post-translational modification by hyperphosphorylation (58) or by association with a feedback regulatory protein (59). Research is under way into the regulation of GTP cyclohydrolase I activity during the development of the zebrafish and in particular to explain why this activity starts to decrease at around 72-h postfertilization, which coincides with the production of xanthophore pteridine pigments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that stimulation of GTPCH activity in mammalian cell culture occurs through phosphorylation and that GTPCH serves as a substrate for both casein kinase II and protein kinase C (32,33). However, specific sites of phosphorylation have not yet been identified in mammalian GTPCH, nor has the effect of phosphorylation been defined enzymatically.…”
mentioning
confidence: 99%